Analisis Unsur Intrinsik Dalam Antologi Cerpen Balon Keinginan Sebagai Bahan Ajar Menulis Karangan Narasi - Wafa Lu'luah; Widjojoko; Deni Wardana (Jurnal Perseda : Jurnal Pendidikan Guru Sekolah Dasar, 2022)
The intrinsic element is one of the most important elements in writing narrative essays. This study intends to analyze the intrinsic elements in the short story anthology of Balon Wish as an alternative to making teaching materials for writing narrative essays in the fifth grade of elementary school. Researchers conducted research using qualitative research with content analysis methods because this study analyzed the intrinsic elements in the book Anthology of Short Stories Anak Balon Wish which would then be followed by an analytical technique process consisting of three stages, namely data reduction, data description, and making conclusions. The purpose of this study was to find out the intrinsic elements in the short story anthology balloon wishes and to obtain teaching materials for writing narrative essays for students in class V of Elementary School based on the results of the analysis of intrinsic elements in short story anthology of short story children of balloon wishes. Based on the results of the study, the intrinsic elements were found, namely, the main character, theme, additional character, time setting, characterizations, place setting, atmosphere setting, plot, point of view of the first person, mandate, and point of view of the third person. From the data described, conclusions are then drawn to make teaching materials for writing narrative essays for students in class V Elementary School in the form of handouts containing material intrinsic elements, writing narrative essays and student worksheets as an exercise to determine the level of student understanding.